2000
DOI: 10.1159/000016599
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Profiles in Dental Plaque in vivo Formed on Fluoride Pre–Treated Human Enamel

Abstract: Using a novel device capable of generating plaque in vivo on a natural enamel substrate, it has been possible to determine fluoride profiles from the saliva–plaque interface towards the enamel surface. Fluoride profiles in dental plaques tended to fall from the saliva–plaque interface towards the enamel. The device also offered the possibility of examining fluoride distributions after pre–treatment of the enamel with fluoride in vitro. Fluoride profiles were determined in plaque generated in vivo on enamel sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
7
0
2
Order By: Relevance
“…When the enamel disks on which the plaque biofilms formed were pretreated with a 900 ppm (ca. 47 mM) solution of fluoride, the profile in the biofims was modified so that there was a peak of fluoride near the biofilm–enamel interface [1]. Thus, it seemed that enamel had the potential to serve as a source of fluoride for plaque biofilms.…”
Section: Weak‐acid Effects On Cells In Biofilmsmentioning
confidence: 99%
“…When the enamel disks on which the plaque biofilms formed were pretreated with a 900 ppm (ca. 47 mM) solution of fluoride, the profile in the biofims was modified so that there was a peak of fluoride near the biofilm–enamel interface [1]. Thus, it seemed that enamel had the potential to serve as a source of fluoride for plaque biofilms.…”
Section: Weak‐acid Effects On Cells In Biofilmsmentioning
confidence: 99%
“…Hydrophobicity, an important characteristic of hard composites, affects the initial water absorption and the adhesion of oral bacteria. Changing the hydrophobicity of the dental polymer surfaces can also affect the adhesion of oral bacteria [20][21][22][23]27 . The breakdown of the marginal areas between enamel and restorative material can provide potential pathways for bacterial reinfection and recurrence of caries.…”
Section: Introductionmentioning
confidence: 99%
“…Different chemical properties and surface topographies of the various materials may play a role in biofilm formation and influence the differences in composition and general properties from one to another [24][25][26] . Several studies have found that the fluoride added to materials can alter wettability and plaque formation, as well as the adherence of Streptococcus mutans [27][28][29][30] . However, other authors contend that the presence of fluoride on dental materials does not modify the materials' basic characteristics 31,32 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has indicated that much of this appears to be located in the outer regions of the plaque biofilm layer Robinson et al, 1997]. It may be released into plaque from fluoride-treated enamel [Arai et al, 2000]. It is also possible that fluoride in plaque may originate from restorative materials.…”
mentioning
confidence: 99%